Inorganic Mineral Dynamics in Two Medicinal Plants and Their Influence on Body Weight Gain in Experimental Rabbits - Ameenah Hammad,; Fayrouz Khaled, (AlQalam Journal of Medical and Applied Sciences, 2026)
This study compares the macro-mineral composition of Moringa oleifera and Ziziphus spina-christi leaf extracts and evaluates how their inorganic profiles relate to physiological outcomes in rabbits. The elemental analysis revealed marked differences between the two species. Moringa oleifera showed exceptionally high Calcium levels (68302 ± 9689.1 ppm), nearly double those of Ziziphus spina-christi, suggesting strong bio-accumulation of divalent cations within its tissues. In contrast, Ziziphus spina-christi exhibited significantly higher concentrations of Potassium (11272 ± 130.1 ppm) and Magnesium (7316 ± 747.4 ppm), with low variability in Potassium indicating a stable distribution pattern. Correlation analysis highlighted a strong negative relationship between Calcium and both Magnesium and Potassium, reflecting classical ionic antagonism between Ca²⁺ and other cations involved in metabolic and osmotic regulation. A moderate positive association between Potassium and Magnesium suggests coordinated accumulation in metabolically active tissues. Although the trends were chemically consistent, some correlations did not reach statistical significance due to the limited sample size. The independent samples t-test confirmed a significant difference only in Potassium levels (p = 0.026), indicating that Ziziphus is a superior source of this electrolyte. Differences in Magnesium and Calcium were not statistically significant, although Calcium showed a marginal trend favoring Moringa. The unequal variance detected by the Brown–Forsythe test reflects the contrasting mineral accumulation patterns of the two plants. Physiologically, rabbits treated with Moringa oleifera exhibited the greatest increase in final body weight (2113 ± 159.81 g), likely linked to its high Calcium content and its structural role in supporting skeletal growth. Ziziphus spina-christi led to moderate weight gain (1815 ± 106.77 g), consistent with its higher Potassium and Magnesium levels, which primarily support metabolic and enzymatic functions rather than structural tissue development. Overall, the findings indicate that the distinct mineral signatures of the two botanical extracts influence both intracellular ionic balance and growth-related physiological responses.